Decentralised-distributed hybrid voltage regulation of power distribution networks based on power inverters - Wang, Yu (2021)
In modern power distribution networks, voltage fluctuations and violations are becoming two major voltage quality issues due to high-level penetration of stochastic renewable energies (e.g. wind and solar power). In this study, a hybrid control strategy based on power inverters for voltage regulation in distribution networks is proposed. Firstly, a decentralised voltage control is designed to regulate voltage ramp-rate for mitigating voltage fluctuations. As a beneficial by-product, the var capacity from the inverters become smoothed. Then, a distributed voltage control is developed to fairly utilise the var capacity of each inverter to regulate the network voltage deviations. Furthermore, once there is a shortage of var capacity from inverters, on-load tap changers control will supplement to provide additional voltage regulation support. The simulation results on IEEE 33-bus distribution network with real-world data have validated the effectiveness of the proposed voltage regulation method.